ASSESSMENT OF LABOUR PRODUCTIVITY IN ROAD CONSTRUCTION PROJECTS OF PAKISTAN - Salah Alaloul, Wesam; Musarat, Muhammad Ali; Mehmood, Hussain; Altaf, Muhammad (Journal of Civil Engineering, Science and Technology, 2021)
Road construction in Pakistan is booming because of China’s One Belt One Road program. Pakistan is in a developing stage and facing a lot of challenges in construction projects, primarily in labour productivity. This research focuses on the factors affecting labour productivity in road construction projects of Pakistan. A questionnaire was developed to observe the impact of critical factors on labour productivity. Based on the gathered responses, the factors were ranked using the Relative Importance Index (RII). The analysis shows that out of thirty (30) factors, the most important five (5) factors that affect labour productivity on road construction are unskilled workforce, payment delays to labour, tools and equipment shortages, poor communication of supervisor with labours and financial difficulties of owner/contractor. By focusing on these critical issues’ betterment can be made in labour productivity which will directly enhance the projects’ performance.